Optimization of Metal‐Organic Chemical Vapor Deposition Regrown n‐GaN. Issue 3 (4th November 2019) - Leone, Stefano; Brueckner, Peter; Kirste, Lutz; Doering, Philipp; Fuchs, Theodor; Mueller, Stefan; Prescher, Mario; Quay, Ruediger; Ambacher, Oliver
Abstract : GaN devices for high‐frequency and high‐power applications often need n‐doped GaN layers on top of their structures. Such layers can be either grown in an epitaxial reactor or formed by implantation or annealing of Si‐containing layers (e.g., a SiO2 mask). These processes are typically performed at high temperatures, which generate the undesired effect of atom diffusion between the different epitaxial layers; consequently, the electrical performance of the final device will be hampered. Herein, an optimized epitaxial growth process of n‐GaN layers is developed with the focus on minimizing the atom diffusion process, while preserving a high material quality and excellent electrical characteristics, such as very low contact resistance for n‐GaN ohmic contacts or high electron mobility in GaN npin structures. A low growth temperature process combined with improved growth conditions to minimize the incorporation of impurities is successfully optimized and demonstrated on different epitaxial reactors. Abstract : Gallium nitride (GaN) transistors require often highly doped regrown n‐GaN layers. Metal‐organic chemical vapor deposition (MOCVD) is adopted for the epitaxial growth of GaN layers, but it suffers from atom diffusions or impurities incorporation. Herein, regrown ohmic contacts with very low contact resistance or defect‐free n‐GaN on top of p‐GaN layers are demonstrated by an optimized MOCVD regrowth process.